Satisfação dos usuários com as equipes de saúde bucal da atenção primária no Brasil e fatores associados: dados do 3º ciclo do PMAQ-AB - CASTRO, Clécio Miranda (2022)
User satisfaction with health services plays an important role in the consolidation and improvement of public policies, providing advances in the production, management, and evaluation of actions. The objective of this research was to analyze the factors associated with the satisfaction of users who received care from oral health teams of primary health care (PHC) in Brazil. This is a cross-sectional study with data from module III of the External Assessment of the 3rd cycle of the PMAQ-AB (Program to Improve Access and Quality in Primary Care). Users assisted by oral health teams (eSB) who answered yes to questions 5.2.6, 18.1 and 8.11 of module III were included, totaling 50,830 users. To assess users' satisfaction with the service provided by the eSB, a satisfaction indicator dichotomized into yes and no was constructed from five questions present in Block 21 (Satisfaction with care) of module III. Demographic, socioeconomic, access, care coordination, first contact, longitudinally, bonding and integrality with the oral health team were also analyzed. Univariate and multivariate analyzes were performed using Poisson regression with robust variance with four-level hierarchical modeling in order to estimate the prevalence ratios (PR) between the independent variables and the outcome. In the univariate analysis at the four hierarchical levels, those with p lower than 0.20 remained in the model. In the multivariate analysis, the inclusion of new variables from each level was performed using the forward method and kept in the final model for adjustment and confounding control only for those variables with a p value less than 0.10. The regression estimates and the 95% confidence interval were verified at the corresponding level and those with p values less than 0.05 were considered statistically significant. Most users (76.75%) reported being satisfied with the oral health teams of PHC in Brazil. Users over 60 years of age were associated with satisfaction (PR 1.16; 95%CI: 1.12-1.21), non-white (PR 0.97; 95%CI 0.96-0.98) , with higher income (PR 1.06; 95%CI: 1.08- 1.13), complete higher education (PR 1.08; 95%CI 1-1.07), with greater distance from the UBS (PR 0.95 ; 95%CI 0.92-0.98), not followed up by the UBS after referral (PR 0.69; 95%CI 0.67-0.70), without rescheduled consultation (PR 0.93; 95%CI 0.9- 0.95), who were not seen by the same dentist (PR 0.90; 95%CI 0.84-0.95), among those who did not have an extended clinical dental examination (PR 0.95; 95%CI 0.94- 0.97) and without qualified listening in the consultation (PR 0.86; 95%CI 0.79-0.92). Users were satisfied with the services offered by the oral health teams of PHC in Brazil, and it is important to note that satisfaction goes beyond the limits of individual characteristics, being influenced by the contexts in which the services are inserted and the primary attributes of PHC.